Clinical characteristics and outcome of hydrocephalus in neurosarcoidosis: a retrospective cohort study and review of the literature - ten Dam, Leroy; van de Beek, Diederik; Brouwer, Matthijs C. (Journal of neurology, 2022)
Hydrocephalus is reported in approximately one-tenth of neurosarcoidosis patients. However, data on clinical characteristics and outcome are lacking. In this retrospective study, we present 11 patients with neurosarcoidosis and hydrocephalus on neuroimaging. Median age was 52 years and seven were female (64%). Presenting symptoms consisted of headache in 8 out of 11 (73%), vertigo in 5 (46%), gait abnormalities in 4 (36%), diplopia in 2 (18%) and decreased visual acuity in 1 (9%). Cranial imaging showed obstructive hydrocephalus in 10 (91%) and non-obstructive hydrocephalus in 1 (9%) out of 11, obstruction occurred at the level of the fourth ventricle in 6 out of 10 (60%). Treatment consisted of glucocorticoids in all the patients with additional methotrexate or azathioprine in 6 (55%) and infliximab in 1 (9%) patient. Neurosurgical intervention was performed in 10 out of 11 (91%) patients. Treatment led to remission, improvement or stabilization of disease in 9 out of 10 (90%) of patients. One patient died due to cerebral herniation despite neurosurgical decompression and CSF shunting. Median modified Rankin scale score at last follow-up was 2 (range 0–6). A systematic review and meta-analysis of studies on hydrocephalus due to neurosarcoidosis identified 36 patients that compared to our patients had a lower median age at onset and a higher mortality. Acute obstructive hydrocephalus due to neurosarcoidosis is a potentially fatal medical emergency requiring neurosurgical intervention and initiation of immunosuppressive therapy. If patients survive the initial phase, the outcome is generally favorable.